Interfacial tension, morphology and linear viscoelasticity behavior of PP/PS blends - Macaúbas,Paulo H. P. (1999)
Blends of polypropylene and polystyrene compatibilized with styrene-butadiene-styrene (SBS) or styrene-ethylene/butylene-styrene (SEBS) copolymers were studied. The morphology of these blends was studied by Scanning Electron Microscopy. Emulsion curves relating the average radius of the dispersed phase to the concentration of compatibilizer added to the blend were obtained. The rheological behavior of the blends was studied by small amplitude oscillatory shear, and correlated to the morphological observations. The interfacial tension between the components of the blends was evaluated from the rheological data. In addition, the applicability of time-temperature superposition (TTS) method for PP/PS blend was studied.